Long-term management of elderly patients with rheumatoid arthritis treated with tocilizumab: comparison of patients over and under 75 years old - Fautrel, Bruno; Saraux, Alain; Idier, Isabelle; Combe, Bernard (Frontiers in Medicine, 2025)
BackgroundFew real-life long-term data depending on patient age are available in patients starting tocilizumab (TCZ) treatment for rheumatoid arthritis (RA).ObjectivesThis study aimed to compare patient characteristics and long-term management with TCZ in RA patients over and under 75 years of age.MethodsThis real-world study was based on secondary data from the French National administrative Healthcare database (SNDS). Eligible adult patients were diagnosed with a RA, and had a first TCZ delivery between 2015/01/01 and 2016/12/31 (index date). Patient data were extracted for the 4 years prior to the index date, and until 2019/12/31. All data were described according to patient age at the index date (<75 and ≥75 years). Therapeutic lines were described from the index date. Maintenance of TCZ therapy was analyzed using the Kaplan Meier method. Adverse events were described using adjusted Hazard Ratios (aHR; reference: age <75 years).ResultsAmong the 4,290 analyzed patients (mean age: 57 ± 14 years; female: 77.4%), 3,888 (90.6%) were aged <75 years and 402 (9.4%) were older. Most patients were treated with disease-modifying antirheumatic drugs (DMARDs) for more than 1 year prior to TCZ initiation (<75 years: 83.6%, ≥75 years: 69.9%). At the index date, 48.5% of elderly received SC TCZ (<75 years: 58.1%), 66.2% had TCZ monotherapy (vs. 51.2%), and 83.3% corticosteroids (vs. 76.1%). The median time of TCZ maintenance was similar in both groups [ <75 years: 17.9 months, 95% CI (16.6–19.5); ≥75 years: 14.9 months (11.6–18.6)]. Over follow-up, patients aged at least 75 years experienced more severe and opportunistic infections than younger patients [17.7 vs. 6.9 events per 100 patient-year, aHR: 1.80; 95% CI (1.53–2.13)], acute cardiovascular events [5.6 vs. 1.4; 2.13 (1.60–2.83)], hematological complications [2.0 vs. ≤ 1.0; 1.88 (1.22–2.91)], and deaths [4.7 vs. ≤ 1.0; 3.71 (2.64–5.21)], but no differences were observed for hepatitis, cancer, allergic reaction, and digestive perforation.ConclusionThis large French nationwide study conducted in patients who initiated TCZ for RA provide reassuring results for patients aged at least 75 years compared to younger patients, in particular regarding treatment maintenance. No new safety signals were identified in elderly patients.